Selenization of S. cerevisiae increases its protective potential in experimental autoimmune encephalomyelitis by triggering an intestinal immunomodulatory loop - de Campos Fraga-Silva, Thais Fernanda [UNESP]; Mimura, Luiza Ayumi Nishiyama [UNESP]; de Oliveira, Larissa Ragozo Cardoso [UNESP]; dos Santos Toledo, Juliana Helena [UNESP]; Borim, Patrícia Aparecida [UNESP]; Zorzella-Pezavento, Sofia Fernanda Gonçalvez [UNESP]; Alonso, Diego Peres [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; de Oliveira, Carlos Alberto Ferreira; da Fonseca, Denise Morais; Villablanca, Eduardo J.; Sartori, Alexandrina [UNESP] (Springer Nature, 2020)
Multiple sclerosis is an autoimmune disease that affects the myelinated central nervous system (CNS) neurons and triggers physical and cognitive disabilities. Conventional therapy is based on disease-modifying drugs that control disease severity but can also be deleterious. Complementary medicines have been adopted and evidence indicates that yeast supplements can improve symptoms mainly by modulating the immune response. In this investigation, we evaluated the therapeutic potential of Saccharomyces cerevisiae and its selenized derivative (Selemax) in experimental autoimmune encephalomyelitis (EAE). Female C57BL/6 mice submitted to EAE induction were orally supplemented with these yeasts by gavage from day 0 to day 14 after EAE induction. Both supplements determined significant reduction in clinical signs concomitantly with diminished Th1 immune response in CNS, increased proportion of Foxp3+ lymphocytes in inguinal and mesenteric lymph nodes and increased microbiota diversity. However, Selemax was more effective clinically and immunologically; it reduced disease prevalence more sharply, increased the proportion of CD103+ dendritic cells expressing high levels of PD-L1 in mesenteric lymph nodes and reduced the intestinal inflammatory process more strongly than S. cerevisiae. These results suggest a clear gut-brain axis modulation by selenized S. cerevisiae and suggest their inclusion in clinical trials.